Filling in the blanks: Network structure and interbank contagion - Kartik Anand; Ben Craig; Goetz Von Peter (Bank of Canada, 2014)
The network pattern of financial linkages is important in many areas of banking and finance. Yet bilateral linkages are often unobserved, and maximum entropy serves as the leading method for estimating counterparty exposures. This paper proposes an efficient alternative that combines information-theoretic arguments with economic incentives to produce more realistic interbank networks that preserve important characteristics of the original interbank market. The method loads the most probable links with the largest exposures consistent with the total lending and borrowing of each bank, yielding networks with minimum density. When used in a stress-testing context, the minimumdensity solution overestimates contagion, whereas maximum entropy underestimates it. Using the two benchmarks side by side defines a useful range that bounds the cost of systemic stress present in the true interbank network when counterparty exposures are unknown. – – Le réseau de liens financiers est important dans de nombreux segments des secteurs bancaire et financier. Pourtant, dans bien des cas, les liens bilatéraux ne sont pas observés et la méthode de l'entropie maximale est la plus couramment utilisée pour estimer les expositions au risque de contrepartie. Dans leur étude, les auteurs proposent une solution de rechange efficace qui combine des arguments relevant de la théorie de l'information et des arguments économiques pour créer des réseaux interbancaires hypothétiques plus réalistes qui préservent les principales caractéristiques du marché interbancaire original. La méthode consiste à tenir compte des liens les plus probables en fonction de la taille des expositions entre les banques, selon le total des prêts et des emprunts de chacune, afin de générer des réseaux ayant une densité minimale. Dans le contexte des tests de résistance, la méthode axée sur la densité minimale surestime la contagion, alors que celle de l'entropie maximale la sous-estime. En ayant recours aux deux modèles en parallèle, on peut ainsi définir une fourchette utile qui délimite le coût attribuable aux tensions systémiques présentes dans le réseau interbancaire réel lorsque les expositions au risque de contrepartie sont inconnues.
Keywords: G21; L14; D85; C63; 330; Econometric and statistical methods; Financial institutions; Financial stability